Board Structure Problem in Aviation Companies: The Relationship of Political Connection and Multiple Directorship on Firm Performance - Lestari, Marsya Chikita; Utama, Cynthia Afriani (University of Merdeka Malang, 2021)
This study analyzes the relationship between the political connection and multiple directorships of aviation companies’ board members and their firm performance. This research will focus on companies in the aviation sector on a broader subsector than previous studies. It will help the shareholder of the aviation companies determine board structure policies and evaluate the implementations conducted so far. This research uses descriptive statistics and regression analysis for the panel data model. Moreover, this study uses a purposive sampling technique secondary data from the aviation company’s annual reports in the Asia continent for the 2016-2020 period. The results show that the multiple directorships negatively affect firm performance in aviation companies while the board’s political connections positively affect firm performance, measured by its Return on Equity (ROE). In contrast, the multiple directorships and political connections do not impact aviation companies' firm performance measured by their Return on Assets (ROA). Overall, this study in the Asia continent asserts the previous study where the political connection positively affects the airline’s firm performance in the US. The result can support the corporate governance practice of deciding board structure in the aviation sectors in Asia in terms of political connection and multiple directorships.DOI: 10.26905/jkdp.v25i3.5892